Letter (copy) : Assistance to Republican Spaniards - Tewson, Vincent
1949-09-30 038-0002-001 Secretary' s VT/EL/39. 30th September, 1949. Mr. A. I. McPherson, Civil Service Clerical Association, 2, Upper Belgrave Street, London, S.W.1. Dear Mr. McPherson, Assistance to Republican Spaniards. I am sorry for the delay in replying to your letter of the 12th September, but I have only just been able to advise Lady Layton in regard to the attitude which we would take to the suggestion of being responsible for the welfare work on which the National Joint Committee had been engaged. Originally the T.U.C. was never associated with the Spanish Joint Committee dealing with refugees, but at a later stage when the Basque children came over we were associated with that particular project. Eventually the work on behalf of the adults and the children was done by a single Committee, but it was the Basque Children's Trust with which we were concerned. As you know, there are a number of refugee groups in this country with whom we have some contact, but as it is felt that people from another country who come over here and enter an industry should belong to their individual Trade Unions, we have not directly undertaken any work on behalf of the refugees. There is a small Spanish Group recognised by us which has been operating here for many years and it is directly associated with the Pascal Tomas Group of Trade Unionists in Toulouse. I have indicated to Lady Layton that, whilst her 292/946/38/2(I)